Applicable aspects for integrated life cicle management (ILCM) in the case of ALSTOM - Drensky, George (Leadership, Society, Strategic Visions, 2021)
The author conducted an internal investigation in order to determine the level of maturity in regards to ILCM within the company. In parallel, an external investigation on selected companies’ best practices research was also initiated by the author in the area of ILCM. Various organizations in the power plant / energy industry and similar industries segments having product or business profi les similar to ALSTOM Thermal Power were researched and documented, including internet, own public information and selected company interviews. All of this work was complemented by an additional investigation of academia, scientifi c conferences and management literatures.